Acute necrotizing encephalopathy in children: A case report and literature review - Ping Yuan; Min Zhong (Wolters Kluwer Medknow Publications, 2018)
Acute necrotizing encephalopathy (ANE) is a rare clinical-imaging syndrome with unknown etiology, characterized by acute fulminant severe encephalopathy and brain damage with multifocal symmetry. ANE has no specific clinical symptoms and signs, similar to common encephalitis or encephalopathy symptoms. The characteristic brain imaging examination is diagnostically significant. To date, no specific treatment for ANE is available and the prognosis is poor. Here, we reported a typical case of ANE in a child, and where a good outcome was achieved through combined therapy with immunoglobulin and glucocorticoids.